Analysis of Tourism as a Socio-Cultural Phenomenon: Present and Future Consequences - Christos Amoiradis; Efstathios Velissariou; Mariya Stankova (Recent Research Advances in Arts and Social Studies Vol. 9, 2024)
The study presents an analysis of tourism as a socio-cultural phenomenon. It presents a critical analysis of earlier findings on the evolution of tourism as a concept and sheds light on cultural and social factors leading to tourism in its present state as well as its social and cultural impacts, positive and negative. The foundation of global tourism is the movement of people away from their typical surroundings, which enables interpersonal communication. By uniting individuals of various racial backgrounds, tongues, and religious beliefs, it has a positive effect on both the host community and the visitors. International tourism boosts sociocultural exchange between the host and visitor countries and has a positive economic influence on the host nation. Furthermore identifies some sociological and cultural factors that shape the characteristics of tourists and highlights the role of socio-cultural motivations of tourists. The present study is based on the secondary re-analysis of a large set of qualitative data. These are derived from articles published between 2011 and 2021, following a search on scholarly databases with the search keywords: Socio-cultural Tourism, social tourism, cultural tourism. The extracted data are in form of a database with parameters of the year of publication, positive and negative socio-cultural impact of tourism, and findings. The study delves into various social and cultural factors influencing tourism. Social factors like safety, political stability, and family dynamics shape tourist behavior, while cultural factors such as competitiveness and preserving identity fuel tourist desires. Additionally, the study identifies sociological factors like human behavior and lifecycle stages, as well as cultural elements like knowledge and family orientation, shaping tourists’ characteristics and motivations. Furthermore, a critical analysis of literature highlights both positive and negative impacts of tourism. Positives include improved infrastructure and regional image, fostering local pride. However, negatives such as increased crime and cultural decline are noted, along with challenges like unsustainable development and exploitation. Overall, the study emphasizes the complex interplay of social and cultural factors in tourism and the need for balanced, sustainable approaches to mitigate negative impacts.